Benthic Foraminiferal biostratigraphy of the Euphrates Formation (Early Lower Miocene-Middle Miocene) in selected sections, Western Iraq - F. Al-Ghreri, Mohammed (Iraqi Journal of Science, 2023)
Studies of three surface sections of the Euphrates Formation in its type locality Western Iraq, yielded a rich benthic foraminifera. Tabulation of the results showed more or less similar content which are previously studied except for the presence for the first time of Triloculina trigonula Lamark, Triloculina tricarinata D’orbigny in the lower parts and Spirolina cf. cylindracea Lamark in the upper parts. In addition two Biozone established in the studies sections, the lower Ammonia beccarii zone and upper Ammonia beccarii-Borelis melo curdica zone